Construction of a full mouth speculum facilitating oral examinations, bronchoscopy and gastric tubing in elephants - Lueders, Imke; Stremme, Christopher (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2021)
Objective Here we tested the application of a full mouth speculum to sedated elephants in human care to gain access to the oral cavity, the trachea (bronchi) and esophagus (stomach) and therefore improve diagnostic and therapeutic options in elephant medicine. The construction of this oral speculum for elephants and the procedure are described.Material and methods The oral speculum is a steel construction consisting of 2 bite plates of 0.8 × 60.0 × 8.0 cm attached between 2 threaded guiding poles (40 cm). Through crank handles, the metal plates are dispersed once placed between the elephant‘s jaws in front of the molars. The oral speculum was applied in 26 elephants (6,16 Asian elephants, and 1,3 African elephants) during standing sedation.Results All sedated elephants tolerated the positioning of the mouth opener and subsequent manipulations well. The mouth opener was applied for the following procedures: inspection of the oral cavity (n = 2), placing a stomach tube (n = 16), and/or performing endoscopic examinations such as bronchoscopy (n = 20) and/or gastroscopy (n = 8).Conclusion This method provides a new possibility to open the jaws to gain access to the molars, larynx and pharynx in captive elephants without full immobilization. Valuable samples for diagnostics may be obtained or animals medicated via stomach tube with this application.Clinical relevance The mouth opener provides veterinarains with a new option to perform necessary diagnostic and therapeutic procedures around the oral cavity, airways and stomach in captive elephants during standing sedation with no need for a full anaesthesia.
Keywords: Endoscopy; elephant; mouth opener; nasogastric tube; oral cavity